Radiation therapy practice changes in the COVID‐19 pandemic era: A pilot study in California. Issue 11 (26th August 2022) - Liu, Xiaoyu; Zhang, Jennifer; Ruan, Dan; Yu, Amy S.; Sehgal, Varun; Qi, X. Sharon; Barker, Margaret C.; Shen, Zhilei L.; Goetsch, Steve
Abstract: Purpose: This study aims to investigate practice changes among Southern and Northern California's radiation oncology centers during the COVID‐19 pandemic. Methods: On the online survey platform SurveyMonkey, we designed 10 survey questions to measure changes in various aspects of medical physics practice. The questions covered patient load and travel rules; scopes to work from home; new protocols to reduce corona virus disease‐2019 (COVID‐19) infection risk; availability of telemedicine; and changes in fractionation schedules and/or type of treatment plans. We emailed the survey to radiation oncology centers throughout Northern and Southern California, requesting one completed survey per center. All responses were anonymized, and data were analyzed using both qualitative and quantitative research methods. Results: At the end of a 4‐month collection period (July 2, 2021 to October 11, 2021), we received a total of 61 responses throughout Southern and Northern California. On average, 4111 patients were treated per day across the 61 centers. New COVID‐19‐related department and hospital policies, along with hybrid workflow changes, infectious control policies, and changes in patient load have been reported. Results also showed changes in treatment methods during the pandemic, such as increased use of telemedicine, hypofractionation for palliative, breast cancer, and prostate cancer cases; and simultaneous boosts, compared to sequential boosts. Conclusion: Our California radiation oncology center population study shows changes in various aspects of radiation oncology practices during the COVID‐19 pandemic. This study serves as a pilot study to identify possible correlations and new strategies that allow radiation oncology centers to continue providing quality patient care while ensuring the safety of both staff and patients.